Preparation Methods and Perceived Risk of Foodborne Illness Among Consumers of Prepackaged Frozen Vegetables – United States, September 2022 - Michelle Canning; Michael Ablan; Tamara N. Crawford; Amanda Conrad; Alexandra Busbee; Misha Robyn; Katherine E. Marshall (Journal of Food Protection)
Listeria monocytogenes causes listeriosis, a serious infection with a high mortality rate for persons at higher risk for listeriosis. The first Listeria outbreak linked to frozen vegetables occurred in 2016 and resulted in three deaths. Many frozen vegetables are intended to be consumed after cooking. However, data on consumer behavior are sparse. We characterized consumers’ perceptions of contamination of prepackaged frozen vegetables, and preparation methods of prepackaged frozen vegetables to help inform prevention strategies. During September 1–24, 2022, Porter Novelli Public Services conducted the FallStyles survey using the Ipsos KnowledgePanel. Data were weighted to be representative of the U.S. population. Point estimates and 95% CIs were calculated, and differences between respondents were determined using Wald chi square tests. Among 3,008 respondents reporting a preparation and consumption method for frozen vegetables, 8.7% (95% CI = 7.4–10.0%) reported ever consuming the product raw. Respondents who reported having children < 18 years old were more likely to report ever consuming frozen vegetables raw compared with respondents who did not (12.5% vs. 7.4%, p < 0.01). The most reported raw preparation method was adding them directly to a blender for smoothie or juice (5.6%; 95% CI = 4.6–6.7%). Among respondents who reported eating frozen vegetables, 59.6% (95% CI = 57.6–61.6%) reported following package instructions. A third (34.1% [95% CI = 32.2–35.9%]) of respondents agreed that frozen vegetables can be contaminated with germs (like Salmonella, E. coli, and Listeria), with a greater proportion of people with cancer disagreeing compared to those without cancer (32.5% vs 23.4%, p = 0.041). These findings show that some consumers may not be cooking frozen vegetables before eating them. Second, consumers might not be reading instructions on packaging. Both findings highlight the critical importance of preventive controls in the production of frozen vegetables prior to reaching the consumer.